Effect Of Adding Different Levels Of Ginger Powder On The Sensory Parameters Of Berker Frozen Buffalo Meat Discs - Meiytham K, Ali Al-Galiby; Noor M. D. Al Mousawi (University of Thi-Qar Journal of agricultural research, 2022)
This study was conducted in the laboratories of the Department of Animal Production,College of Agriculture / University of Thi Qar for the period from 6/1/2022 to 3/4/2022 to know the effect of adding different levels of ginger powder on the sensory parameters of Berker frozen buffalo meat tablets used for thigh meat, which was purchased From the local markets of the city of Nasiriyah and the experiment was conducted using concentrations of 1, 2 and 3% of ginger powder, which was added to the meat tablets kept by cooling at a temperature of 4 ° C. The sensory tests were conducted, and the results when assessing the sensory criteria led to a moral superiority in the color of buffalo meat in favor of the treatment T2 for the fourth, seventh and ninth days, with averages (9.00, 8.00, and 8.33), respectively, and on the twelfth day, T3 outperformed with an average of (8.67). The moral superiority for the first, fourth, seventh and ninth days was in favor of the T2 treatment, and their averages were (8.67,8.33, 8.67,8.67, respectively), and with regard to freshness, the moral superiority was in favor of the T2 treatment for the fourth, seventh and ninth days, with averages (8.33, 7.67, 8.00 (respectively and on the day). The twelfth treatment T4 outperformed the rest of the treatments with an average of (8.00) The results showed a significant increase in meat juice in favor of the T2 treatment for the fourth, seventh and ninth days with averages of (8.33, 8.00, 8.00) respectively, and on the twelfth and fifth days, treatment T4 outperformed the rest of the treatments with an average It reached (7.33, 7.00), respectively, and the significant increase continued in favor of T2 treatment in general acceptance and for the first, fourth, seventh and ninth days, with an average of (9.00, 9.00, 8.67, 7.67).T3 treatment time was significant and averaged (7.67) for the twelfth day